Pregnancy through the Lens of Breast Cancer Survivors: A Qualitative Study in an Iranian Setting - Azizi, Marzieh; Ebrahimi, Elham; Moghadam, Zahra Behboodi; Shahhosseini, Zohreh; Khorsandi, Behjat; Modarres, Maryam (Current Women's Health Reviews, 2025)
BackgroundAn increasing incidence of breast cancer (BC) among young women aged<40 and also a growing pattern of delay in childbearing decision-making among couples in developed and developing countries leads to considerable concerns regarding the possibility of pregnancy for young BC survivors without children. These women may have had different experiences and needs during pregnancy, which were not assessed in previous studies.ObjectiveThis study was carried out to explore the experiences of pregnancy and perceived needs through the lens of Iranian BC survivors.MethodsIn this qualitative conventional content analysis, sixteen BC survivors at two referral centers in Sari, Mazandaran, Northern Iran, were selected through purposive sampling. Data were collected through in-depth semi-structured interviews, and the content analysis of the interviews was carried out according to Graneheim and Landman's strategies using MAXQDA 2018 software.ResultsThe participant's age mean ± standard deviation was 31.94 ± 3.90 years, and also, the age of participants at BC diagnosis time ranged from 20-33 years (mean ± SD= 25.81 ± 3.50 years). 14 out of 16 participants had one pregnancy after cancer treatment, one survivor had two, and one had three pregnancies experienced after surviving. The result of data analysis led to the extraction of six main categories, including “pregnancy and childbirth problems”, ” mental health problems,” “social problems”, “marital instability”, “need to support,” “need to resort to spirituality,” and 13 subcategories.ConclusionThe results of this study provide significant information regarding the experiences and needs of BC survivors during pregnancy. As pregnancy considered as a stressful occurrence in women's life especially in BC survivors, attention to their concerns and needs is an important issue which should be addressed. These women need to a special attention and follow up during pregnancy by their midwife or gynecologist. In addition, promoting the healthcare providers' information regarding the pregnancy consequences among these women is vital to providing high-quality maternal care to them.
Keywords: Pregnancy